Penyuluhan Fisioterapi Komunitas Edukasi dan Penanganan Cedera Olahraga Terhadap Siswa MA AL-HIDAYAH Karangploso Malang - Halief Rahmadillah Akbar; Atika Yulianti; Nanik Zainiyah (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Sports injuries in adolescents are a common aspect that is often experienced by the average adolescent, both male and female. Ankle sprain or ankle injury is an injury that is often experienced by teenagers when doing heavy or light sports activities. One of the treatments for sports injuries is using the PRICE method Protect (protect), Rest (rest), Ice (ice), Compress (bandage), Elevate (elevate). The purpose of this study was to increase understanding related to proper handling of sports injuries in adolescents by conducting socialization activities to deliver the material for handling these injuries, to measure the level of understanding of these students by using a pre-test questionnaire at the beginning of the activity and a post-test after the end of the activity. The results of the research that has been conducted on students and schoolgirls show an increased level of understanding with an average percentage of 5.12% and the post-test value after the delivery of the material increases with a percentage of 90%, the results of this percentage are a calculation of all questions ranging from 1-10 between the results of the post test and pre-test.